2018
DOI: 10.1016/j.neuroscience.2018.03.030
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for Lymphotactin (XCL1) Signaling in the Nervous System: XCL1 Acts via its Receptor XCR1 to Increase Trigeminal Neuronal Excitability

Abstract: HighlightsWe identified XCR1 in the peripheral and central nervous systems and demonstrated its upregulation following nerve injury.In injured nerve, XCR1 is present in nerve fibers, CD45-positive leucocytes and Schwann cells.In Vc, XCR1 labeling is consistent with expression in terminals of Aδ- and C-fiber afferents and excitatory interneurons.XCL1 increases neuronal excitability and activates intracellular signaling in Vc, a pain-processing region of the CNS.These data provide the first evidence that the XCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 65 publications
3
26
0
Order By: Relevance
“…The findings can be explained by the fact that chemokines are able to promote migration and fusion of the monocyte lineage in vitro through increasing the of integrin α9β1( 2 ). Another possibility to explain the promoted osteoclastogenesis in our study might be that activation of XCL1-XCR1 axis initiates PI3K/AKT, MEK, and JNK signaling pathways in a variety of cells ( 25 , 26 ). These signaling pathways are involved in regulation of osteoclasts differentiation and bone resorption activity.…”
Section: Discussionmentioning
confidence: 89%
“…The findings can be explained by the fact that chemokines are able to promote migration and fusion of the monocyte lineage in vitro through increasing the of integrin α9β1( 2 ). Another possibility to explain the promoted osteoclastogenesis in our study might be that activation of XCL1-XCR1 axis initiates PI3K/AKT, MEK, and JNK signaling pathways in a variety of cells ( 25 , 26 ). These signaling pathways are involved in regulation of osteoclasts differentiation and bone resorption activity.…”
Section: Discussionmentioning
confidence: 89%
“…Based on their analysis, XCL1-XCR1 axis is involved in the peripheral and central trigeminal pain pathway. In other words, induction of c-FOS, extracellular signal-regulated kinase, and PP38 expression and also hyper-excitability within the trigeminal subnucleus caudalis nociceptive circuitry compose the possible proposed mechanism (Bird et al, 2018).…”
Section: )mentioning
confidence: 99%
“…Similar results were obtained in rodent models of TBI, and recent experimental studies have shown significant changes in some chemokines, e.g., CCL2, CCL3, CCL4, CCL9, CCL11, CX3CL1, and CXCL5 [ 1 , 7 , 8 ], however, there is still a lack of knowledge about X-C motif chemokine ligand 1 (XCL1, also known as lymphotactin and SCM-1alpha). XCL1 acts through X-C motif chemokine receptor 1 (XCR1), which is a G-protein coupled receptor [ 9 ] that has been detected in neurons [ 10 , 11 ]. It was shown that after mental nerve damage the XCR1 is upregulated at the site of the injury—the authors proposed XCL1 as an excitability factor in orofacial pain [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…XCL1 acts through X-C motif chemokine receptor 1 (XCR1), which is a G-protein coupled receptor [ 9 ] that has been detected in neurons [ 10 , 11 ]. It was shown that after mental nerve damage the XCR1 is upregulated at the site of the injury—the authors proposed XCL1 as an excitability factor in orofacial pain [ 11 ]. Importantly, XCL1 is produced not only by immune cells [ 12 ], but also by neurons [ 10 , 11 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation